Corrosion of novel Pb–Mg–Al–B nuclear shielding alloy in fluoride medium. (February 2015) - Bai, M.; Sun, Y.; Duan, Y. H.
<x content-type="archive" xml:space="preserve">Abstract</x> Five kinds of Pb–Mg–Al–B alloys with B atomic fraction of 0, 1·84, 3·62, 5·36 and 7·06% were prepared by induction melting. The corrosion behaviour of Pb–Mg–Al–B in 3·5 wt-%NaF solution was investigated by immersion tests, neutral salt spray and electrochemical measurements. The surface morphology and corrosion products of alloys were measured using scanning electron microscopy (SEM), X-ray diffraction and X-ray photoelectron spectroscopy. Results show that the Pb–Mg–Al–B alloy with 5·36%B shows the best corrosion resistance; the volume fraction and distribution of Mg2Pb, Mg17Al12 and other phases affect the corrosion resistance significantly; the major corrosion products are Mg17Al12, Pb, PbO, Al2O3, etc., and Mg is apt to form a microgalvanic cell with Mg2Pb (Mg2Pb–Mg) in corrosive solution, and a bit of product of MgF2 film has a role to protect alloys; and the different corrosion resistances are caused by the different microstructure of alloys with different B additions.